Keterlibatan Amerika Serikat dan Iran dalam Konflik Di Suriah Pasca Arab Spring - Ahmad Zainal Mustofa (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2021)
This article describes about rivalry two great powers between the United States and Iran in Syria’s conflict. The rivalry that occurs between the US and Iran is due to motive of interest in Syria. These interests make them have to confront by taking advantage of political destabilization that has occurred in Syria. The US and Iran used the civil war in Syria for their national interests, especially political influence and natural resources. In this study, the author uses the theory of proxy war to analyze the US-Iran rivalry. Then the method used is descriptive analytical. This study seeks to answer the question of what is the background of the Syrian conflict and its impact on US-Iran involvement? The conclusion in this study is the occurrence of the Arab Spring in Syria due to public dissatisfaction with the leadership of the Bashar al-Assad regime. The group that did not like Assad then formed a stronghold of the government opposition. This opposition stronghold was then exploited by the United States which had an interest in overthrowing Assad. Seeing this situation, Iran, which is Syria's partner, took a stand to support the pro-government camp. As a result, the confrontation of the two countries through a proxy war in Syria is inevitable. Not only the US-Iran, this conflict also involves their allied countries. Finally, the conflict from civil war to proxy war in Syria is inevitable